AMYLOLYTIC ACTIVITY OF THE HEPATOPANCREAS OF ORATOSQUILLA NEPA - SREEJA, J.; GEETHA, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
Amylolytic activity of hepatopancreas of Oratosquilla nepa at different parameters like temperature, pH, enzyme concentration and substrate concentration were carried out. Enzyme activity at different enzyme concentration varied from 4.27 mg/g protein/ minute to 13.16 pg/ minute. Maximum activity was ato.4 ml enzyme concentration. Increase in substrate showed increase in enzyme activity pH even though showed two peaks, maximum activity occurred at pH 8. The temperature maximum observed in amylase activity of O. nepa was 33°C. These findings show that digestive amylase of O. nepa is well adapted to its ambient water.